Co-authorship with Community Partners as Knowledge Co-creation - Fursova, Julia (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2023)
This report from the field provides reflection on the author’s experience of co-authoring a peer-reviewed manuscript with community partners for publication in an academic journal. The report reflects on the existential, logistical, and process-related challenges of applying community-based research and delivering its promise of knowledge co-creation while grappling with inequities imbedded in the realities of academic and non-academic life. Reflecting on the lessons learned, this paper probes into further considerations for the operationalization of ethical principles for equitable collaboration in community-based research.